Biological activity of various extracts and phenolic content of Micromeria persica and M. hedgei - A. Sonboli (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Lamiaceae members have long been used in Iranian Traditional Medicine (ITM) for their various medicinal properties. The main objective of this study was to evaluate the antioxidant capacity and antimicrobial activity as well as the total phenolic content (TPC) of the various extracts and fractions of two Iranian endemic Micromeria (M. persica and M. hedgei). Methods: Plant materials were extracted with methanol by maceration for 24 h. Then, the methanol extract (ME) was further fractionated to obtain the chloroform (M-C) and water (M-W) fractions. The antimicrobial activity was investigated against seven Gram-positive and -negative bacteria and three fungi. Antioxidant activity was evaluated by DPPH method and the data were compared with their total phenolic contents. Results: The nonpolar sub fractions (M-C) of both plants were active against pathogens especially Staphylococcus epidermidis and Bacillus subtilis with equal MIC values of3.75 and 7.5 mg/mL, respectively. Antioxidant activity evaluation showed that the polar fractions of both Micromeria species were stronger than nonpolar fractions, while the more considerable effect was observed for the water soluble fraction of the extract for M. hedgei with IC50 value of 59.1 µg/mL in comparison to M. persica (IC50 = 76.3 µg/mL). The highest gallic acid equivalent (GAE) total phenolic contents was found to be 263.5 ± 1.5 and 256.3 ± 3.1 mg/g dry weight for M-W extracts of M. hedgei and M. persica, respectively. Conclusion: The results indicated that the two species might be suggested as new potential sources of natural antioxidant and antimicrobial agents.